Ridesharing: The state-of-the-art and future directions - Furuhata, Masabumi; Dessouky, Maged; Ordóñez, Fernando; Brunet, Marc-Etienne; Wang, Xiaoqing; Koenig, Sven (Transportation research. Part B: methodological, 2013)
•We provide a taxonomy and classification of current ridesharing systems.•The classification reveals issues with the state of the art ridesharing systems.•Literature review provides current limitations of ridesharing systems.•We demonstrate future directions of ridesharing systems. Although ridesharing can provide a wealth of benefits, such as reduced travel costs, congestion, and consequently less pollution, there are a number of challenges that have restricted its widespread adoption. In fact, even at a time when improving communication systems provide real-time detailed information that could be used to facilitate ridesharing, the share of work trips that use ridesharing has decreased by almost 10% in the past 30years. In this paper we present a classification to understand the key aspects of existing ridesharing systems. The objective is to present a framework that can help identify key challenges in the widespread use of ridesharing and thus foster the development of effective formal ridesharing mechanisms that would overcome these challenges and promote massification.